2015
DOI: 10.3233/rnn-140489
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cumulative high-frequency rTMS on freezing of gait in Parkinson’s disease

Abstract: Purpose: Freezing of gait (FOG) affects mobility and balance seriously. Few reports have investigated the effects of repetitive transcranial magnetic stimulation (rTMS) on FOG in Parkinson’s disease (PD). We investigated the efficacy of high-frequency rTMS for the treatment of FOG in PD. Methods: Seventeen patients diagnosed with PD were recruited in a randomized, double-blinded, cross-over study. We applied high frequency rTMS (90% of resting motor threshold, 10 Hz, 1,000 pulses) over the lower leg primary mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
115
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(124 citation statements)
references
References 34 publications
4
115
2
3
Order By: Relevance
“…Despite of the cortico‐cortical connections with the parietal and premotor cortices’ involvement in visuo‐motor control of action and the crucial role of DLPFC in the cognitive control of motor behavior (Kim et al., ), our meta‐analysis did not show significant motor benefit after rTMS over the DLPFC in terms of the UPDRS‐III scores. Other studies showed no effect of rTMS over DLPFC on clinical Parkinsonian symptoms, motor performance of ballistic wrist movements,or synergistic effects of motor signs improvement of rTMS over DLPFC+M1 (Conditions TNCCfC, ).…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…Despite of the cortico‐cortical connections with the parietal and premotor cortices’ involvement in visuo‐motor control of action and the crucial role of DLPFC in the cognitive control of motor behavior (Kim et al., ), our meta‐analysis did not show significant motor benefit after rTMS over the DLPFC in terms of the UPDRS‐III scores. Other studies showed no effect of rTMS over DLPFC on clinical Parkinsonian symptoms, motor performance of ballistic wrist movements,or synergistic effects of motor signs improvement of rTMS over DLPFC+M1 (Conditions TNCCfC, ).…”
Section: Discussioncontrasting
confidence: 66%
“…There was insufficient information to categorize the blind procedure in two studies (del Olmo et al., ; Sedlackova et al., ). Nine studies (Benninger et al., , ; Brys et al., ; Hamada et al., ; Khedr et al., ; Kim et al., ; Lomarev et al., ; Sedlackova et al., ; Shirota et al., ) described the dropout number.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…35, 36 Our cerebellar site, identified based on lesions that cause FOG, is also closely connected to the leg area of M1 (Figure 5A). This finding is consistent with the notion that targets of brain stimulation may be brain networks rather than single regions.…”
Section: Discussionmentioning
confidence: 81%